2013
DOI: 10.1155/2013/390824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sputtering Parameters on the Film Properties of Molybdenum Back Contact for CIGS Solar Cells

Abstract: Molybdenum (Mo) thin films are widely used as a back contact for CIGS-based solar cells. This paper determines the optimal settings for the sputtering parameters for an Mo thin film prepared on soda lime glass substrates, using direct current (dc) magnetron sputtering, with a metal Mo target, in an argon gas environment. A Taguchi method with an L9orthogonal array, the signal-to-noise ratio, and an analysis of variances is used to determine the performance characteristics of the coating operation. The main spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…For a given deposition pressure the Mo film resistivity reduces as power increases in agreement with other reports [20][21][22]. …”
Section: Mo Growth and Na Diffusionsupporting
confidence: 92%
“…For a given deposition pressure the Mo film resistivity reduces as power increases in agreement with other reports [20][21][22]. …”
Section: Mo Growth and Na Diffusionsupporting
confidence: 92%
“…Substrates and targets are the material basis for preparing thin films by sputtering, and they are the primary factors to be considered for magnetron sputtering [82]. Substrate temperature directly affects the crystalline phase and crystal structure of the deposited films, so substrate temperature is critical for the photoelectrical properties of film [75,82].…”
Section: Effect Of Substrate Temperature On Properties Of Zno:ga Filmsmentioning
confidence: 99%
“…Miyaka [85] reported that the increase of substrate temperature is helpful for Zn's replacement by Ga and the improvement of crystal quality. Higher substrate temperature helps the desorption of adsorbed oxygen in grain boundaries, which can effectively prevent the formation of Ga2O3 in the Substrates and targets are the material basis for preparing thin films by sputtering, and they are the primary factors to be considered for magnetron sputtering [82]. Substrate temperature directly affects the crystalline phase and crystal structure of the deposited films, so substrate temperature is critical for the photoelectrical properties of film [75,82].…”
Section: Effect Of Substrate Temperature On Properties Of Zno:ga Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report of a DSSC by O'Regan and Grätzel, in 1991 [8], they have been intensively studied as a potential replacement for standard solar cells because of their relatively high efficiency and low cost [9], compared with p-n junction photovoltaic devices [10,11]. A typical DSSC consists of dye molecules that act as sensitizers, a porous TiO 2 layer, a fluorine-doped tin oxide (FTO) substrate, an electrolyte charge carrier, and a platinized FTO substrate as a so-called counter electrode or cathode.…”
Section: Introductionmentioning
confidence: 99%